The Use of Probiotics in Gastrointestinal Disease - Karen L Madsen (Canadian Journal of Gastroenterology)
Probiotics are living microorganisms that can affect the host in a beneficial manner. Prebiotics are nondigestible food ingredients that stimulate the growth and activity of probiotic bacteria already established in the colon. Efficacy of probiotic compounds has been shown in a wide range of gastrointestinal diseases. Lactobacillus GG alone, or the combination of Bifidobacterium bifidum and Streptococcus thermophilus, is effective in the treatment of Clostridium difficile, as well as in preventing the frequency and severity of infectious acute diarrhea in children. Prevention of antibiotic-induced diarrhea with the concomitant administration of either Lactobacillus GG or Saccharomyces boulardii has been demonstrated. The most successful studies involve the use of Lactobacillus GG at a dose of 1×1010 viable organisms per day and the yeast boulardii at a dose of 1 g/day. A probiotic preparation (VSL#3 - 6 g/day) that uses a combination of three species of Bifidobacterium, four strains of Lactobacillus and one strain of Streptocccus has shown promise in maintaining remission in ulcerative colitis and pouchitis, as well as in preventing the postoperative recurrence of Crohn's disease. The mechanism of action of probiotics may include receptor competition, effects on mucin secretion or probiotic immunomodulation of gut-associated lymphoid tissue. Oral administration of probiotic compounds has been demonstrated to be well tolerated and safe. However, while probiotics have the potential to improve human health and to prevent and treat some diseases, major improvements are needed in labelling and quality assurance procedures for probiotic compounds. In addition, well planned and controlled clinical studies are necessary to delineate fully the potential for probiotic compounds.